Peptide hormones in plants - Zhenbiao Zhang; Huibin Han; Junxiang Zhao; Zhiwen Liu; Lei Deng; Liuji Wu; Junpeng Niu; Yongfeng Guo; Guodong Wang; Xiaoping Gou; Chao Li; Chuanyou Li; et al. (Molecular Horticulture)
Abstract Peptide hormones are defined as small secreted polypeptide-based intercellular communication signal molecules. Such peptide hormones are encoded by nuclear genes, and often go through proteolytic processing of preproproteins and post-translational modifications. Most peptide hormones are secreted out of the cell to interact with membrane-associated receptors in neighboring cells, and subsequently activate signal transductions, leading to changes in gene expression and cellular responses. Since the discovery of the first plant peptide hormone, systemin, in tomato in 1991, putative peptide hormones have continuously been identified in different plant species, showing their importance in both short- and long-range signal transductions. The roles of peptide hormones are implicated in, but not limited to, processes such as self-incompatibility, pollination, fertilization, embryogenesis, endosperm development, stem cell regulation, plant architecture, tissue differentiation, organogenesis, dehiscence, senescence, plant-pathogen and plant-insect interactions, and stress responses. This article, collectively written by researchers in this field, aims to provide a general overview for the discoveries, functions, chemical natures, transcriptional regulations, and post-translational modifications of peptide hormones in plants. We also updated recent discoveries in receptor kinases underlying the peptide hormone sensing and down-stream signal pathways. Future prospective and challenges will also be discussed at the end of the article.